Crisis, unemployment and poverty: analysis of life trayectories and strategies in the labour market - Arnal, María; Finkel, Lucila; Parra, Pilar (Cuadernos de Relaciones Laborales, 2013)
From the financial and economic crisis that is fully established in 2008 in Spain, precariousness and labor deregulation have largely increased. Using qualitative methodology, this article examines the impact of the crisis on workers who have lost their jobs and have scarce economic resources. To this end we have identified four main trajectories from which we analyze the different ways of perceiving the crisis, meanings and attitudes towards the labor market and its potential link with processes of greater impoverishment. Finally, from these trajectories we reconstruct various strategies that are deployed to get back into the labor market.